Evaluation of Alkali-Activated Mortar Incorporating Combined and Uncombined Fly Ash and GGBS Enhanced with Nano Alumina - Barham Ali (Salehan Institute of Higher Education, 2024)
The present research focuses on assessing the fresh and hardened properties as well as the durability performance of alkali-activated mortar in an ambient environment and the impact of integrating nano-alumina (NA) at a 2% ratio as a substitute for binder materials in alkali-activated mortar (AAM). Additionally, it assesses the effectiveness of alkali-activated mortar employing different blends of ground granulated blast furnace slag (GGBS) and fly ash as environmentally friendly substitute building materials. Fly ash (FA), ground granulated blast slag (GGBS), and an equal mixture of GGBS and FA make up these binder ingredients. As a result, the main binders contain GGBS, FA, or a 50/50 mixture of GGBS and FA. The sodium hydroxide (NaOH) concentration is fixed at a 12-molarity level, and the alkali activator solution to binder ratio is kept at 0.5. In the alkali solution, the ratio of sodium silicate to sodium hydroxide is always 2.5. The study evaluates various properties of AAM, such as compressive strength, flowability, unit weight, flexural tensile strength, and durability, under ambient conditions at a steady room temperature of 23±3°C. Results indicate that AAM mixtures devoid of NA exhibit a higher flow rate compared to those containing NA. Nonetheless, the flowability of AAM mixtures aligns well with standard requirements, being modest yet adequate. Significantly, the inclusion of NA enhances the mechanical properties and durability of AAM, demonstrating its beneficial effects. Doi: 10.28991/CEJ-2024-010-03-016 Full Text: PDF